2023
DOI: 10.3390/audiolres13050070
|View full text |Cite
|
Sign up to set email alerts
|

Otological Planning Software—OTOPLAN: A Narrative Literature Review

Annalisa Gatto,
Margherita Tofanelli,
Ludovica Costariol
et al.

Abstract: The cochlear implant (CI) is a widely accepted option in patients with severe to profound hearing loss receiving limited benefit from traditional hearing aids. CI surgery uses a default setting for frequency allocation aiming to reproduce tonotopicity, thus mimicking the normal cochlea. One emerging instrument that may substantially help the surgeon before, during, and after the surgery is a surgical planning software product developed in collaboration by CASCINATION AG (Bern, Switzerland) and MED-EL (Innsbruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…High resolution CT scans showed only nine electrodes in the cochlea and seven in the range of speech frequencies. OTOPLAN software (see review by Gatto et al, 2023 ) indicated that Electrode 1 (E1) was at the 957 Hz spiral ganglion (SG) frequency, E4 at 2393 Hz and E7 at 7173 Hz. As a consequence, it was reasonable to suspect that both electrode pitch and speech quality matches would be upshifted.…”
Section: Discussionmentioning
confidence: 99%
“…High resolution CT scans showed only nine electrodes in the cochlea and seven in the range of speech frequencies. OTOPLAN software (see review by Gatto et al, 2023 ) indicated that Electrode 1 (E1) was at the 957 Hz spiral ganglion (SG) frequency, E4 at 2393 Hz and E7 at 7173 Hz. As a consequence, it was reasonable to suspect that both electrode pitch and speech quality matches would be upshifted.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies conducted within the last five years have showcased impressive results, demonstrating the effective implementation of OTOPLAN within patient populations and highlighting its benefits in clinical contexts. These studies are nicely presented in Gatto’s review [ 42 ].…”
Section: Clinical Applications and Surgical Planning Utilizing 3d Inn...mentioning
confidence: 99%